Газодинамічні характеристики електричних розрядів в імпульсному генераторі плазми з індуктивно-ємнісним накопичувачем енергії - Дубовенко, К.В. (Технічна електродинаміка, 2012)
Numerical simulation of powerful electrical discharges in the air in the circuit with the inductive and capacitive energy store and electroexplosive opening switch has been carried out with one-dimensional magnetohydrodynamic approach. Electrical, energetical and gasodynamical characteristics of the discharge have been obtained. With accounting for the electrical processes and electrical energy dissipation in the plasma load the analysis of the gasodynamical transients has been carried out. In particular, spatial and temporal dependencies of the medium pressure, velocity and density under conditions of the magnetic pressure and discharge current skinning influence have been shown.